On the spectral expansions of distributions connected with Schrodinger operator. - Rakhimov, Abdumalik A.; Akhmedov, Anvarjon; Hishamuddin, Zainuddin (Elsevier, 2012)
In this work the spectral expansions of the distributions connected with Schrodinger operator are investigated. The localization principle of Riesz means of spectral expansions of distributions f from the Sobolev space